Dynac Sdn Bhd / Noor Azreen Ain Abd Azis - Abd Azis, Noor Azreen Ain (Faculty of Business and Management, 2023)
Most Universities in Malaysia require students to complete Industrial Training for at least one semester in the final year of study before they are eligible to graduate from a degree program. The purpose of this internship program is to prepare students with the insight of the real working industry so that after they graduate from the university, they at least require some experiences in terms of skills and knowledge as well as the real views of how the working environment would look like because it is totally different from what they had been experienced during their study journey. It is also one of the ways that help students increase their chances in getting a job after graduation. Student have been given the opportunity to undergo 24 weeks of industrial training at the chosen company. Students may discover that working in the industry require s several kinds of positive Attitudes such as resilient, dedication, discipline, punctuality, and even more, which possibly can be achieved over a 24-week internship period before joining a real-world employment in the near future. Throughout the internship period, students are supervised by the supervisor who will assist and evaluates their performance during the train in g period. It is the responsibility of the supervisor to guide and assign duties, assist students, and ensure they obtain feedback from their learning and work experiences throughout their 24-week of industrial training at the company. Engaging with supervisor assists students in improving their interpersonal and cooperation skills, which are essential for their career in the future. The supervisor will assess, and grade students based on their performance during the industrial training as this evaluation me assures the students' achievements and competency in the workplace.